A comparison of hexachlorophene and Lactacyd on growth of skin flora in healthy term newborn infants - McHattie, J. C. (1974)
Reports of toxicity from the routine bathing of newborn infants with hexachlorophene resulted in discontinuing its use in the newborn nurseries of the Ottawa Civic Hospital, only to be followed by an outbreak of skin infections. As a result, a controlled trial of bathing newborn babies with either Lactacyd or pHisoHex was begun. The efficacy of the soaps was evaluated by comparing the colonization of the nose and umbilical cords of 158 pHisoHex-washed babies and 156 Lactacyd-washed babies on the day of discharge from hospital. The gram-negative and gram-positive bacterial flora of nose and cord of infants washed with pHisoHex and Lactacyd were identical in frequency and distribution.